An Integrated Management System for a Medical Center - G.K.B.V. Karunathilake; G.A.T.T. Wijesinghe; H.M.W.T.C.B. Samarakoon; A.U. Ovitigala; D. I. De Silva; H.M.P.P.K.H. Samarasekara (International Journal of Engineering and Management Research, 2022)
Recently, the use of technology in medicine and healthcare has increased, particularly during the pandemic period. This adaptation has shown to be fruitful in many scenarios. Implementing a computerized system to manage daily tasks like handling patient records, appointments and other administrative tasks can result in an efficient system. This will in turn result in a better experience for the patients as well as the staff members. This research paper documents the development process of creating an online web application for an existing manual medical center management system. The previous system made simple and frequent tasks like retrieving laboratory results or checking a doctor’s appointment a time-consuming hassle. Further, the requirement of a digitized system to track the medical staff was evident as many incorrect appointments and patient records were detected. This proposed system provides the benefits of appointment management, laboratory management, staff management, payment management. This solution makes it easier to check staff profiles and schedule appointments for patients, preventing making an appointment for a doctor on a day. Additionally, the laboratory division may post reports and this system manages all the patient payment details. The proposed system's functionalities will next be discussed, along with the testing methodologies and outcomes.